Parallel generalized real symmetric-definite eigenvalue problem - Sims, James S.; Ruiz, María Belén (Journal of Research of the National Institute of Standards and Technology, 2020)
A computationally fast Fortran 90+ quadruple precision portable parallel GRSDEP (generalized real symmetric-definite eigenvalue problem) package suitable for large (80,000 x 80,000 or greater) dense matrices is discussed in this paper.
CRIS-Team Scopus Importer:2020-12-18
Keywords: Dense matrix eigensolver; High precision; Parallel